Subjetividad, estructura y sistema penal - Garbe, Verónica Analía (2010)
The goal of this work is to discuss how the discourse on social reality\nis shaped by those holding power, thus leading the establishment to be reproduced.\nIn order to achieve this, an epistemological view that interrelates structure\nand subjectivity will be taken. Special emphasis will be laid on the operation of\npower agencies , mainly on those constituting the criminal justice system, and on\nhow they operate in practice, and in analyzing such agencies, primary attention\nwill be drawn on communication used as a tool to build and consolidate an established\norder. The importance we attach to social classes and how these interact\nwith the operating agencies of power will also be taken into account. In turn, we\nwill deal with the discourse produced by the agencies recreating communication\nstereotypes that affect the social corpus